A New Implantation Method for Orthodontic Anchor Screws: Basic Research for Clinical Applications - Reiko Tokuyama-Toda; Hirochika Umeki; Shinji Ide; Fumitaka Kobayashi; Shunnosuke Tooyama; Mai Umehara; Susumu Tadokoro; Hiroshi Tomonari; Kazuhito Satomura (Biomedicines, 2023)
This study aimed to determine whether the positional relationship between the underside of the screw head and the surface of the alveolar bone could alter the stress on the two surfaces and affect the stability of implanted anchor screws. First, in order to confirm the extent of the gap between the mini-screw and the bone surface, a mini-screw was placed in the palate of rabbits and examined histologically. As a result, in the conventional screw implantation procedure, oral mucosa between the base of the screw head and the bone creates a spatial gap. Removal of the oral mucosa eliminates this gap. Then, we compared the positional difference of the screw in a contact and gap group by analyzing stress distribution on the bone and screw. Analysis using the finite element method showed that more stress was loaded on both the bone and screw in the gap group than in the contact group. Cortical bone thickness did not affect stress in either group. The effects of different load strengths were similar between groups. A surgical procedure in which mucosal coverings are removed so that implanted anchor mini-screws are in contact with the bone surface was found to reduce the stress load on both the bone and screw. This procedure can be used to prevent undesirable dislodgement of implanted mini-screws.